Estado nutricional, consumo de alimentos y actividad física en personal militar de la Fuerza Aérea del Perú recuperados del COVID 19 - Hurtado Gómez, Gelem Anabel (2024)
The objective of this study was to determine the relationship between food consumption and physical activity with nutritional status in military personnel of the Peruvian Air Force of Air Group No. 42 recovered from COVID 19 Iquitos – 2023. The study had a quantitative, non-experimental approach, descriptive, correlational and cross-sectional. The type of sampling was non-probabilistic, for convenience. A total of 100 active military personnel were selected. A nutritional sheet, international physical activity questionnaire (IPAQ), and frequency of food consumption were used. The results report that FAP military personnel were 41% overweight for females and 42% for males. In Glucose, 86% presented normal values. 27% of mild or moderate anemia was observed between both sexes. In the percentage of fat, the optimum in the total range is 41% between the two sexes, the moderate fat mass index there is a total between both sexes is 31%, the military personnel presented a regular food consumption or need changes with a 11 % in females and 89% in males. In addition, 27% low physical activity, 43% moderate physical activity and 30% high physical activity. Concluding that there is a statistical relationship between body mass index, hemoglobin and fat percentage with food consumption and physical activity, however, no statistical relationship was found with glucose level.